Starting Out: qualitative perspectives of new graduate nurses and nurse leaders on transition to practice. (27th February 2017) - Regan, Sandra; Wong, Carol; Laschinger, Heather K.; Cummings, Greta; Leiter, Michael; MacPhee, Maura; Rhéaume, Ann; Ritchie, Judith A.; Wolff, Angela C.; Jeffs, Lianne; Young‐Ritchie, Carol; Grinspun, Doris; et al.
Abstract : Aim: To describe new graduate nurses' transition experiences in Canadian healthcare settings by exploring the perspectives of new graduate nurses and nurse leaders in unit level roles. Background: Supporting successful transition to practice is key to retaining new graduate nurses in the workforce and meeting future demand for healthcare services. Method: A descriptive qualitative study using inductive content analysis of focus group and interview data from 42 new graduate nurses and 28 nurse leaders from seven Canadian provinces. Results: New graduate nurses and nurse leaders identified similar factors that facilitate the transition to practice including formal orientation programmes, unit cultures that encourage constructive feedback and supportive mentors. Impediments including unanticipated changes to orientation length, inadequate staffing, uncivil unit cultures and heavy workloads. Conclusions: The results show that new graduate nurses need access to transition support and resources and that nurse leaders often face organisational constraints in being able to support new graduate nurses. Implications for Nursing Management: Organisations should ensure that nurse leaders have the resources they need to support the positive transition of new graduate nurses including adequate staffing and realistic workloads for both experienced and new nurses. Nurse leaders should work to create unit cultures that foster learning by encouraging new graduate nurses to ask questions and seek feedback without fear of criticism or incivility.